The Analysis of Accounting Treatment of Account Receivable Based on PSAK No. 50 and PSAK No. 55 at PT Wahana Boga Nusantara - Anak Agung Gek Sri Bawani; I Gusti Ayu Astri Pramitari; Ketut Nurhayanti (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
The purpose of this study is to analyse and compare the accounting treatment of account receivable applied by PT Wahana Boga Nusantara with PSAK No. 50 and No. 55 revisied in 2014. This study uses descriptive data analysis techniques with a qualitative approach. The data collection method used is an interview with the Manager of the Financial Department and the Head of Account Receivable section on receivables accounting policy. The treatment of receivables accounting, non participant observations, and documentation with the documents used are financial position statements, profit and loss statements, receivables age lists, recapture of credit sales data during 2020. This study showed that the recognition of receivables has been by PSAK number 55 the revised the year 2014 because receivables are recognized when goods have been shipped and received by customers. Meanwhile, the measurement and presentation of receivables are not appropriate because they are not measured and presented at fair value.